Prediction of consolidation from reduced consolidation testing time / Mohd Hanaffi Ayop - Ayop, Mohd Hanaffi (1980)
This experimental project describes the results of consolidation test carried out on two different nature of testing procedure, that is a 'reduced consolidation testing time' and 'normal consolidation testing time'. The correlation between the two said testing procedure is being determined. This is an attempt to make a study on possibility of reducing the normal consolidation testing time. Properties of soil related to consolidation arc being investigate and their relation to consolidation are being sought. The results of total consolidation using S .B TAN method, which is a simpler approach for determination of total consolidation are being discussed. Apart from consolidation test alone, the investigations also made used of the seive analysis test, hydrometer test, specific gravity test, atterberg limit test and moiture content test.